Implementasi Kurikulum 2013 Mata Pelajaran Bahasa Inggris di SMP Negeri 9 Madiun - Munif, Dian Nashrul (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2015)
The aims of this study Wet to describe the qualitative based on curriculum 2013. Data sources used include documents, information, place and events or Activities such as teaching and learning Indonesian in SMPN 9 Madiun, and the results of questionnaires to determine the perceptions of techers regarding curriculum in 2013. Techniques of data collection are done through observation, interviews, document analysis, and questionnaires. Test the validity of data is done by triangulation. The result showed that perception of teachers about the curriculum in 2013 is less good. It has an impaction the Manufacturer of instructional plannig and implementation of learning. In the learning plan it impacts on learning Activities that run less than maximum. On learning Activities are constrain including saintific approach, the assessment has been not fully implemented is addition, the lack in the infrastructure support and the lack ofÂ involvement of the student is also an obstacle in implementation of learning therefore it take various Measures to overcome these constraints.